2012
DOI: 10.1093/nar/gks1150
|View full text |Cite
|
Sign up to set email alerts
|

Animal QTLdb: an improved database tool for livestock animal QTL/association data dissemination in the post-genome era

Abstract: The Animal QTL database (QTLdb; http://www.animalgenome.org/QTLdb) is designed to house all publicly available QTL and single-nucleotide polymorphism/gene association data on livestock animal species. An earlier version was published in the Nucleic Acids Research Database issue in 2007. Since then, we have continued our efforts to develop new and improved database tools to allow more data types, parameters and functions. Our efforts have transformed the Animal QTLdb into a tool that actively serves the researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
388
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 371 publications
(397 citation statements)
references
References 6 publications
7
388
1
1
Order By: Relevance
“…Previous studies have reported quantitative trait loci (QTL) for IMF in several breeds (Hu et al, 2013). Comparison with QTL detected in previous studies showed some agreement with 18 of our consensus selection signatures, but candidate regions on SSC 3, 9 (92.2-123.6 Mb), 13, 14, 15, and 16 were ex clusively identified in our study.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have reported quantitative trait loci (QTL) for IMF in several breeds (Hu et al, 2013). Comparison with QTL detected in previous studies showed some agreement with 18 of our consensus selection signatures, but candidate regions on SSC 3, 9 (92.2-123.6 Mb), 13, 14, 15, and 16 were ex clusively identified in our study.…”
Section: Discussionsupporting
confidence: 87%
“…With more and more QTLs having been integrated, a QTL database (Hu et al, 2013) can be a potential resource for studying the genetic mechanisms that underlie growth and immune traits. Until now, there are more than 500 growth-related QTLs and~300 immunity-related QTLs in the pig QTL database.…”
Section: Introductionmentioning
confidence: 99%
“…To date, more than 1500 QTLs, covering most of the genome, have been found to be associated with growth traits (Hu et al, 2013). Previous genomic studies have generally employed low-density microsatellites as markers.…”
Section: Introductionmentioning
confidence: 99%